Highly effective 525 nm femtosecond laser crosslinking of collagen and strengthening of a human donor cornea. (13th December 2017) - Shavkuta, B S; Gerasimov, M Y; Minaev, N V; Kuznetsova, D S; Dudenkova, V V; Mushkova, I A; Malyugin, B E; Kotova, S L; Timashev, P S; Kostenev, S V; Chichkov, B N; Bagratashvili, V N
Abstract: A two-photon laser femtosecond crosslinking process at the wavelength of 525 nm was studied in a human donor cornea in the presence of riboflavin using two-photon optical microscopy and nanoindentation. It was shown that such an approach results in efficient crosslinking of the corneal collagen and a significant (three-fold) increase in the Young's modulus of the corneal structure. Application of a femtosecond laser with the wavelength of 525 nm allows a drastic enhancement of efficiency in the presence of riboflavin on human corneas and a 50-fold reduction of the laser treatment duration in comparison with the use of a femtosecond laser with the wavelength of 760 nm. We relate this effect to a significant growth in the coefficient of two-photon absorption due to the laser wavelength falling within the edge of the photoinitiator (riboflavin) absorption band. Our studies on a donor human cornea demonstrate the good potential for the clinical application of a femtosecond laser with the wavelength of 525 nm for increasing the cornea rigidity using the two-photon laser femtosecond crosslinking technique.